2012
DOI: 10.1097/htr.0b013e31824ee1a8
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Sleep Disturbance Following Traumatic Brain Injury—Their Nature, Causes, and Potential Treatments

Abstract: These findings suggest potential treatments including cognitive behavior therapy supporting lifestyle modifications, pharmacologic treatments with modafinil and melatonin, and light therapy to enhance alertness, vigilance, and mood. Controlled trials of these interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(150 citation statements)
references
References 54 publications
6
139
1
4
Order By: Relevance
“…49,50 This may be because those with mild TBI retain more self-awareness. 7 Insult to the brain is considered a determinant of sleep disturbances, however, no convincing neuroimaging evidence has linked location of cerebral injury with sleep disturbance. 51,52 Although some studies have failed to show that injury severity is a predictor of sleep deficits following TBI, 3,11,24 recent research suggests that intracranial hemorrhage and lower Glasgow Coma Scores are strongly associated with increased sleep need, suggesting that widespread cerebral trauma contributes to sleep disturbances post TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 This may be because those with mild TBI retain more self-awareness. 7 Insult to the brain is considered a determinant of sleep disturbances, however, no convincing neuroimaging evidence has linked location of cerebral injury with sleep disturbance. 51,52 Although some studies have failed to show that injury severity is a predictor of sleep deficits following TBI, 3,11,24 recent research suggests that intracranial hemorrhage and lower Glasgow Coma Scores are strongly associated with increased sleep need, suggesting that widespread cerebral trauma contributes to sleep disturbances post TBI.…”
Section: Discussionmentioning
confidence: 99%
“…6 While individuals with TBI are known to report sleep problems, 1 the specific changes to sleep remain poorly characterized. 7 Studies have been limited by small sample sizes, with variable and inconsistent findings. [8][9][10][11][12] This makes for a difficult characterization of sleep post TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic treatments have also been studied. Although not addressing sleepiness per se, Ponsford et al [90] found that morning bright light therapy improved general fatigue in patients with mTBI.…”
Section: Hypersomnolencementioning
confidence: 99%
“…Sleep-wake regulating centers and associated pathways are damaged in TBI, and these damages will be the cause of disturbances of sleep architecture. Sleep disturbances contribute to fatigue, which may be associated with mental slowness and, slowed information processing [32]. Sleep disturbances also contribute to anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%